Fundamentals of Entrpreneurship ENT300 Chosch Enterprise / Phylisia Valerie Beard... [et al.] - Beard, Phylisia Valerie; Mawan, Leminang; Zakaria, Siti Nurhafizah; Brahim, Mohammad Aqmal; Md. Salim, Mohd. Shahid (2019)
Our company’s name is CHOSCH ENTERPRISE. The business is in the form of partnership which is consisting of five members. Each partner contributes certain amounts of cash agree in our agreement. Our main services are washing and cleaning of vehicles. Our company comes out with the new technology for washing and cleansing vehicles. Self-service vacuum car is also provided by our company with new and high technology machine available in town which only requires 10 minutes of process. The purpose of our business is we want to be known in as a QUICKLEEN AUTOWASH in the same line with other businesses that produce the same business. Although there are many bigger company outside there that also open up a car wash service as their own business, but, we are confident that our business can be a successful one in the future. Our business’ aimed is getting the customer to be more familiar to the business and make sure our customer will feel easy to wash their vehicles when needed. |